Analysis of financial decisions through mathematical programming - Villarreal Satama , Freddy Lenin (2022)
The present work has the purpose of generating an investment portfolio proposal based on the linear programming methodology with the use of the simplex method with the two-phase modeling technique. For this, the data of Forex table 5 of investments that helped to establish the six variables of the model, each one representing the type of investment of the portfolio, are taken. The results indicate that after maximizing the investment in the objective function, its result is USD 67,790 and that a sensitivity analysis can subsequently be generated based on the amount that the investor wishes to risk.